Strategi Humas dalam Pembentukan Citra Perguruan Tinggi Swasta - Nunung Misran; Mujahid Mujahid; Fitriana Fitriana (Yayasan Pendidikan Penelitian Pengabdian Algero, 2024)
The purpose of this study was to examine and obtain an overview of the Role and Strategy of Public Relations in shaping the image of higher education. Study at Andi Djemma University Palopo. This research uses a case study with a qualitative descriptive approach by conducting an interview study, while the theory used is symbolic interaction and information organization. The results showed that the Public Relations of Andi Djemma University Palopo tried to carry out its duties as a mediator to bridge the relationship between college elements. Building a college image uses mass media to build relationships with internal and external parties. The strategy used in building the image of higher education is to utilize technology, increase the capacity of human resources and provide educational information to the public in the field of Tri Dharma Perguruan Tinggi. Research from Andi Djemma University found that the role of PR is always trying to improve the image of the institution. In order to continue to gain the trust of the user community, college public relations are aware that they must always try to maintain the image of the college they represent. PR tries to carry out its duties as a mediator to bridge the relationship between elements of higher education.